Cancer-Associated Fibroblast (CAF) expression in Metastatic and Non-metastatic Oral Squamous Cell Carcinoma (OSCC) - A determinant in cancer progression - et al., Prof. Dr. Balakrishnan Sekar (International Journal of Advanced Science and Technology, 2019)
Background: Tumour stroma plays a vital role in carcinogenesis. Myofibroblastic expression in stromal fibroblast (cancer-associated fibroblast, CAF) is associated with poor clinical outcome was observed in previous studies.Aim: To evaluate and compare the expression of alpha smooth muscle actin (α-SMA) in non-metastatic and metastatic oral squamous cell carcinoma (OSCC).Materials and Methods: A retrospective study was conducted in 100 formalin fixed, paraffin embedded tissue blocks which includes 50 metastatic and 50 non-metastatic OSCC. α-SMA expression was observed on the basis of proportion and intensity in the tumour stroma.Results: α-SMA shows significantly increasing expression from non-metastatic to metastatic OSCC. Statistically significant expression of α-SMA (p<0.001) was observed in metastatic OSCC. Conclusion: Expression of α-SMA in tumour stroma suggests a positive role of myofibroblast in tumour progression and a potential target for the therapeutic purpose.